Enhancing Phase Measurement by a Factor of Two in the Stokes Correlation - Yadav, Amit; Sarkar, Tushar; Suzuki, Takamasa; Singh, Rakesh Kumar (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Phase loss is a typical problem in the optical domain, and optical detectors only measure the amplitude distribution of a signal without its phase. However, an optimal phase is desired in a variety of practical applications, such as optical metrology, nondestructive testing, and quantitative microscopy. Several methods have been proposed to quantitatively measure phase, among which interferometry is one of the most commonly used. An intensity interferometer has also been used to recover phase and enhance the phase difference measurement via the intensity correlation. In this paper, we present and examine another technique based on the Stokes correlation for enhancing phase measurement by a factor of two. The enhancement in phase measurement is accomplished through an evaluation of the correlation between two points of Stokes fluctuations of randomly scattered light and by recovering the enhanced phase of the object by using three-step phase shifting along with the Stokes correlations. This technique is expected to be useful for imaging and the experimental measurement of the phase of a weak signal.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: coherence; phase imaging; speckle; vortex beam